If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+1-(-2)-(-x)=2-2x
We simplify the equation to the form, which is simple to understand
2x+1-(-2)-(-x)=2-2x
Remove unnecessary parentheses
2x+1+2-(-x)=2-2x
Remove unnecessary parentheses
2x+1+2+1x=2-2x
We move all terms containing x to the left and all other terms to the right.
+2x+1x+2x=+2-1-2
We simplify left and right side of the equation.
+5x=-1
We divide both sides of the equation by 5 to get x.
x=-0.2
| R=5w-15 | | F(x)=2x^2+11x+12 | | A=(2x+1)(4x-3) | | 4(p+5)=5(p-7) | | -3m+23-2(m-1)=9m-(6m-8)-5m+2 | | 7-(x-4)=8 | | -(9z-(14z+4))=4+(4z+1) | | q-3r-s=p | | 3(2x+3)-10x=7-(8x-2) | | (1/5)^-1 | | Kw^2-13x-5=0 | | (x+3)(x+3)+289=0 | | 5b+4=2b+11+5 | | 47J^2-20J=0 | | -2x+2=5x-64 | | 4-(x+7)=8 | | -x+8=5x-18 | | 1/6:1/8:1/24= | | 2x-4(x-5)=14 | | 7+5(2x-8)=-13 | | -5y-10=3y+22 | | 3x+2=12+5x | | 3x+6(-8x+4)=-21 | | 7x^3/4 | | 8/3.5x | | 1=3x+2+x | | 6+x-7x=-24 | | 15=0.375(z-5) | | 126=(7-x)(12-x) | | ln(2x)-ln(3x-1)=0 | | (3x-4)^2/(x-1) | | 4(X-3)-7+2X=7X+11-X |